Abstract 233: First‐line Techniques for Endovascular Therapy of Primary Distal medium Vessel Occlusion Stroke: A Matched Analysis - Mahmoud H. Mohammaden; Hend Abdelhamid; Mohamed R. Dohiem; Stavros G. Matsoukas; Johanna Fifi; Bradley J. Gross; Alhamza R. Al‐Bayati; Marta Olive‐Gadea; Marc Rodrigo‐Gisbert; Andre Monteiro; James M. Siegler; Mudassir Farooqui; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Previous studies did not show a difference in terms of safety and efficacy among first‐line stent retriever (SR), contact aspiration (CA), or combined techniques for proximal large vessel occlusion strokes. However, the optimal reperfusion therapy in patients with primary distal medium vessel occlusion (DMVO) strokes is uncertain. We aimed to compare the clinical and procedural outcomes among first‐line SR, CA and combined techniques in patients with primary DMVO. Methods This is a retrospective analysis of a prospectively maintained database from 14 comprehensive stroke centers in the US and Europe. Patients were included if they had a primary DMVO stroke due to MCA‐M3/M4, ACA‐A1/A2‐3, or PCA‐P1/P2‐3 and underwent mechanical thrombectomy with first‐line SR, CA, or combined technique. The primary outcome was FPE defined as eTICI 2c/3 on the first pass. Secondary outcomes included mFPE defined as eTICI 2b/3 on the first pass, successful reperfusion defined as eTICI 2b/3 at the end of the procedure. Clinical outcomes included 90‐day mRS0‐1 and 90‐day mRS0‐2. Safety measures included procedural complications, symptomatic intracranial hemorrhage (sICH), and 90‐day mortality. The secondary analysis aimed to identify the procedural and clinical outcomes in 3 matched cohorts: (SR vs. CA), (SR vs. combined technique), and (CA vs. combined technique). Results A total of 365 patients were eligible for analysis; 38.1% were female, with a mean age of 69.3 years and a median NIHSS score of 11 [7‐18]. The first‐line SR group consisted of n=74 (20.3%), CA group n=142 (38.9%), and combined technique group n=149 (40.8%). Patients with first‐line SR or combined technique had a lower median NIHSS score, less frequent MCA‐M3 segment occlusion, and less usage of the rescue strategy compared to those with first‐line CA, P<0.05. Patients with first‐line CA had less frequent BGC usage and lower rates of FPE and procedural complications compared to first‐line SR or combined technique, P<0.05. Successful reperfusion at the end of the procedure was similar among the 3 groups (Figure). On multivariable analysis, there was no difference in terms of primary, secondary outcomes, or safety measures among the 3 first‐line techniques, except for higher procedural complications in patients who underwent the first‐line combined technique compared to those with first‐line CA (aOR 3.66, 95% CI [1.25‐10.75], P=0.02). The matched analyses did not show any difference in the primary outcome: (1) (SR, n=54 vs. CA, n=54) FPE; 31.5% vs. 26.9%, P=0.61, aOR 1.33, 95% CI [0.57‐3.11], P=0.52), (2) (SR, n=72 vs. combined technique, n=54) FPE; 37.5% vs. 31.9%, P=0.48, aOR 1.48, 95% CI [0.73‐3.03], P=0.28), and (3) (CA, n=109 vs. combined technique, n=109) FPE; 24.1% vs. 25.7%, P=0.78, aOR 0.94, 95% CI [0.50‐1.74], P=0.84). Similarly, there was no difference in terms of secondary outcomes and safety measures. Conclusion Our study suggests that in patients with primary DMVO, first‐line SR, CA, and combined techniques have a similar rate of FPE with no differences in final reperfusion or clinical outcomes. Randomized clinical trials are warranted